2021
DOI: 10.3390/cancers13102410
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Postoperative Changes in Sarcopenia on Long-Term Survival in Non-Metastatic Colorectal Cancer Patients

Abstract: The effect of perioperative sarcopenic changes on prognosis remains unclear. We conducted a retrospective cohort study with 2333 non-metastatic colorectal cancer patients treated between January 2009 and December 2012 at the Asan Medical Center. The body composition at diagnosis was measured via abdominopelvic computed tomography (CT) using Asan-J software. Patients underwent CT scans preoperatively, as well as at 6 months–1 year and 2–3 years postoperatively. The primary outcome was the association between pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
(64 reference statements)
3
13
0
Order By: Relevance
“…Cox proportional hazards regression analysis identified sarcopenia as an independent factor contributing to worse OS. The findings in this study are consistent with the conclusions in the review by Lee et al 38 that the 5‐year OS (95.8% vs. 92.1%, HR = 2.234, p < 0.001) and recurrence‐free survival (93.2% vs. 86.2%, HR = 2.251, p < 0.001) rates were lower in patients with preoperative sarcopenia). In addition to sarcopenia, age >70 years and alcohol consumption were independent factors for OS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cox proportional hazards regression analysis identified sarcopenia as an independent factor contributing to worse OS. The findings in this study are consistent with the conclusions in the review by Lee et al 38 that the 5‐year OS (95.8% vs. 92.1%, HR = 2.234, p < 0.001) and recurrence‐free survival (93.2% vs. 86.2%, HR = 2.251, p < 0.001) rates were lower in patients with preoperative sarcopenia). In addition to sarcopenia, age >70 years and alcohol consumption were independent factors for OS.…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have been conducted to evaluate the effects of sarcopenia on the survival of colon cancer patients after surgery, but the findings have been inconsistent. Some studies found that sarcopenia was a predictor for worse OS, [29][30][31][32][33][34][35][36][37][38] but some others found that sarcopenia was not associated with OS. [39][40][41] Discrepancies in the prognostic contributions of sarcopenia might be in part due to differences in the methods used to determine sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the clinical significance of sarcopenia in cancer has attracted increasing attention. The associations between sarcopenia and the prognosis in patients with gastric cancer ( 10 ), colorectal cancer ( 11 ), lung cancer ( 12 ), ovarian cancer ( 13 ), and HCC ( 14 , 15 ) have been investigated. For example, a cohort study revealed that sarcopenic patients with HCC undergoing TACE had a significantly poorer overall survival (OS) than those without sarcopenia (491 vs. 1,291 days, P = 0.017) ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 , 10 ] Sarcopenia has also emerged as an important prognostic factor for various cancers and is reported to be associated with a poorer survival outcome in both colon and rectal cancer. [ 11 , 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Sarcopenia has also emerged as an important prognostic factor for various cancers and is reported to be associated with a poorer survival outcome in both colon and rectal cancer. [11,12] We speculated that regulating a patient's lifestyle after colorectal cancer surgery may help to further improve survival outcomes and also the health-related quality of life (HRQOL). However, this would be difficult to achieve with the routine post operative management protocols used currently in these cases.…”
Section: Introductionmentioning
confidence: 99%